Local level epidemiological analysis of TB in people from a high incidence country of birth - Massey Peter D; Durrheim David N; Stephens Nicola; Christensen Amanda (BMC, 2013)
Abstract Background The setting for this analysis is the low tuberculosis (TB) incidence state of New South Wales (NSW), Australia. Local level analysis of TB epidemiology in people from high incidence countries-of-birth (HIC) in a low incidence setting has not been conducted in Australia and has not been widely reported. Local level analysis could inform measures such as active case finding and targeted earlier diagnosis. The aim of this study was to use a novel approach to identify local areas in an Australian state that have higher TB rates given the local areas' country of birth profiles. Methods TB notification data for the three year period 2006-2008 were analysed by grouping the population into those from a high-incidence country-of-birth and the remainder. Results During the study period there were 1401 notified TB cases in the state of NSW. Of these TB cases 76.5% were born in a high-incidence country. The annualised TB notification rate for the high-incidence country-of-birth group was 61.2/100,000 population and for the remainder of the population was 1.8/100,000. Of the 152 Local Government Areas (LGA) in NSW, nine had higher and four had lower TB notification rates in their high-incidence country-of-birth populations when compared with the high-incidence country-of-birth population for the rest of NSW. The nine areas had a higher proportion of the population with a country of birth where TB notification rates are >100/100,000. Those notified with TB in the nine areas also had a shorter length of stay in Australia than the rest of the state. The areas with higher TB notification rates were all in the capital city, Sydney. Among LGAs with higher TB notification rates, four had higher rates in both people with a high-incidence country of birth and people not born in a high-incidence country. The age distribution of the HIC population was similar across all areas, and the highest differential in TB rates across areas was in the 5-19 years age group. Conclusions Analysing local area TB rates and possible explanatory variables can provide useful insights into the epidemiology of TB. TB notification rates that take country of birth in local areas into account could enable health services to strategically target TB control measures.